Review of the scientific and methodological seminar Synergetic Approach in State Understanding: Challenges and Development - Aelita M. Mongush; Valentina S. Nikitina (RUDN Journal of Law, 2023)
On December 15, 2022, the Department of Theory of Law and the State of the Law Institute of the RUDN University held a scientific and methodological seminar on the Synergistic Approach in State Understanding: Challenges and Development. A wide range of people were involved in the seminar: the faculty of the department, graduate students of the department and students of the Law Institute. The work of the seminar suggested personal and remote presence of the participants and observers.